The Rare Case of a COVID-19 Pregnant Patient with Quadruplets and Postpartum Severe Pneumonia. Case Report and Review of the Literature - Răzvan Socolov (MDPI AG, 2021)
Background and Objectives: The multiple pregnancies associated with COVID-19 is a new and difficult condition to manage. The prognosis for rapid deterioration after the cesarean delivery is difficult to assess and needs close interdisciplinary follow-up due to pregnancy and postpartum-related changes. Materials and Methods: We report the case of a 37-year-old primigesta primipara patient who was admitted to “Elena Doamna” Clinical Hospital of Obstetrics and Gynecology at 33 weeks and 3 days of gestation with high-grade multiple pregnancies (triplets) for threatened premature birth associated with COVID-19. The patient had a history of surgically corrected atrial septal defect during childhood and currently is known to have paroxysmal supraventricular tachycardia. Tocolysis was ineffective and the decision to perform a cesarean operation was made. The diagnosis was established: primigesta, primipara, at 34 weeks of gestation, high-grade multiple pregnancy with triplets, intact membranes, threatened premature birth, surgically corrected atrial septal defect, paroxysmal supraventricular tachycardia, infection with COVID-19. The patient underwent a cesarean intervention and treatment for COVID-19 pneumonia. The intervention took place at 33 weeks and 4 days of gestation resulting in four newborns with weights between 1400 g and 1820 g and Apgar scores between 6–8. All newborns were transferred to a third-degree Neonatology ICU service due to their prematurity. The fourth newborn was not identified in any of the ultrasounds performed during pregnancy. During the postpartum period, the patient had a fulminant evolution of COVID-19 pneumonia, with rapid deterioration, needing respiratory support and antiviral treatment. Discussions: Managing high-risk obstetrical pregnancies associated with COVID-19 requires a multidisciplinary team consisting of obstetricians, anesthesiologists, neonatologists, and infectious disease doctors. Conclusion: Our case is the first to our knowledge in Romania to present an association of high-grade multiple pregancy with COVID19 moderate form, rapidly evolving postpartum, needing rapid intensive care admission, and specific treatment with Remdesivir, with good post-treatment evolution.